Accountability, Transparency, and Participation in Village Fund Management - Yudastio Yudastio; Niar Azriya (Jurnal Sains Sosio Humaniora, 2022)
This study aims to examine whether there is a relationship between the principles of accountability, transparency, and participation with the management of village funds in Natar District, South Lampung Regency. This study looked at the extent to which villages apply the principles of Good Governance in managing village funds in running village government. This is by enacting Law no. 6 of 2014 concerning the Financial Management of Village Funds. The population in this study was the villages of Natar District, South Lampung Regency. The analysis method uses multiple linear regression with SPSS Version 25. Based on the results of hypothesis testing using the Pearson correlation test using SPSS v25 software, only one hypothesis is supported, namely the accountability variable. At the same time, the other two hypotheses, namely, the variables of transparency and participation, are not supported. The management of village funds in villages in Natar District, South Lampung Regency is good enough to apply the principles and rules regarding accountability. However, the principles of transparency and participation in the management of village funds are still not maximally implemented.